Technological Advancements and Their Strategic Impact on Management Practices - Ayu Listiyani, Renita; Mustagfiroh, Alif; Maulana, Hilmi; Damar Ichwandani, Restu (International Journal of Law Social Sciences and Management, 2024)
Technological advancements have fundamentally transformed management practices within organizations. The study aims to analyze the strategic impact of technological progress on management practices through a literature review method. Based on a comprehensive literature analysis, the study identifies that information and communication technology (ICT), data analytics, artificial intelligence (AI), automation, and cloud computing play crucial roles in enhancing operational efficiency, data-driven decision-making, and innovation. ICT, through ERP and CRM systems, facilitates business function integration, improves coordination, and enhances information accuracy. Data analytics and AI enable managers to make more informed and timely decisions. Automation and robotics increase production accuracy and allow a focus on strategic tasks. Digital technology alters customer interactions, expands marketing reach, and improves customer experience. Cloud computing supports work mobility and more efficient collaboration. However, technological advancements also bring challenges such as cybersecurity and data privacy, requiring effective change management strategies. The study concludes that the success of technology implementation depends on managers' ability to align technology with business strategy and develop comprehensive plans. Recommendations for managers include enhancing technological knowledge, fostering an innovation culture, investing in cybersecurity, adopting flexible approaches, and focusing on customer experience. With the right approach, technology can be a key driver of competitive advantage in a dynamic market. This research provides valuable insights for managers in developing strategies to leverage technological advancements to achieve organizational goals and improve overall performance.